"Brace technology" thematic series - the Gensingen brace™ in the treatment of scoliosis - Weiss, Hans-Rudolf (BioMed Central, 2010)
BACKGROUND: Bracing concepts in use today for the treatment of scoliosis include symmetric and asymmetric hard braces usually made of polyethylene (PE) and soft braces. A new asymmetric Chêneau style CAD/CAM derivate has been designed to overcome problems the author experienced with other Chêneau CAD/CAM systems over the recent years. BRACE DESCRIPTION: This CAD/CAM Chêneau derivate has been called Gensingen brace™, a brace available to address all possible curve patterns. Once the patients' trunk is scanned with the help of a whole trunk optical 3D-scan and the patients' data from the clinical measurements are recorded, a model of the brace can be created by (1) modifying the trunk model of the patient 'on screen' to achieve a very individual brace model using the CAD/CAM tools provided or by (2) choosing a brace model from our library and re-size it to the patients' properties 'on screen'. RESULTS: End-result studies have been published on the Chêneau brace as early as 1985. Cohort studies on the Chêneau brace are available as is a prospective controlled study respecting the SRS criteria for bracing studies, demonstrating beneficial outcomes, when compared to the controls using a soft brace. Sufficient in-brace correction effects have been demonstrated to be achievable when the Chêneau principles of correction are used appropriately. As there is a positive correlation between in-brace correction and the final outcome, the Chêneau concept of bracing with sufficient in-brace corrections as published can be regarded as being efficient when applied well. Case reports with high in-brace corrections, as shown within this paper using the Gensingen brace™ promise beneficial outcomes when a good compliance can be achieved. CONCLUSIONS: The use of the Gensingen brace™ leads to sufficient in-brace corrections, when compared to the correction effects achieved with other braces, as described in literature. According to the patients' reports, the Gensingen brace™ is comfortable to wear, when adjusted properly. Further studies are necessary (1) in order to evaluate brace comfort and (2) effectiveness using the SRS inclusion criteria.